DIGITAL TWINS: TRANSFORMING URBAN PLANNING AND INFRASTRUCTURE MANAGEMENT - Ravi Dara; Muhammad Syaiful; Chenda Dara (Cognitionis Civitatis et Politicae, 2025)
The rapid advancement of digital technologies has paved the way for innovative approaches in urban planning and infrastructure management. Digital twins, virtual replicas of physical entities, have emerged as a transformative tool in these fields, allowing for real-time monitoring and analysis.This research aims to explore the potential of digital twins in enhancing urban planning and infrastructure management. Specifically, it investigates how these technologies can improve decision-making processes, optimize resource allocation, and foster sustainable urban development. A mixed-methods approach was employed, combining quantitative data analysis from existing digital twin projects with qualitative case studies. Data were collected from various urban environments utilizing digital twins, focusing on metrics such as efficiency, cost savings, and stakeholder engagement. The findings reveal that digital twins significantly enhance urban planning by providing precise simulations of urban environments. Case studies demonstrated improved decision-making capabilities, leading to a 30% increase in resource efficiency and a 25% reduction in project costs. Stakeholder engagement also improved, with participants reporting higher satisfaction levels due to transparent processes. Digital twins represent a paradigm shift in urban planning and infrastructure management. The integration of real-time data and predictive analytics provides urban planners and managers with valuable insights, enabling more informed decisions. This research underscores the importance of adopting digital twin technologies to foster sustainable urban development and improve the overall quality of life in cities. Further studies are recommended to explore the long-term impacts of digital twin implementations across diverse urban contexts.